The Role of Information and Communication Technology in Enhancing Teaching-Learning Outcomes: A Comparative Analysis of Government and Private Colleges in Uttar Pradesh - Chaturvedi, Kabita Kumari; Bisaria , Charu; Dwivedi, Prabhat Kumar (International Review of Management and Marketing, 2025)
This research examines the impact of Information and Communication Technology (ICT) integration on teaching-learning outcomes across government and private colleges in Uttar Pradesh, India. Through a mixed-methods approach involving surveys (n=486) and interviews (n=32) with faculty and students from 12 institutions, this study analyzes disparities in ICT infrastructure, usage patterns, and resultant educational outcomes. Findings reveal significant differences in ICT adoption between institution types, with private colleges demonstrating more comprehensive implementation yet government institutions showing greater relative improvements in student performance when ICT is effectively deployed. The study identified key barriers to ICT integration including funding constraints, technical support limitations, and faculty technological competency. Statistical analysis confirmed a positive correlation (r=0.74) between ICT integration level and student performance across all institutions. This research contributes to understanding educational technology dynamics in developing regions and provides evidence-based recommendations for policy makers to address the digital divide in higher education.